ANALISIS KEMAMPUAN BERPIKIR TINGKAT TINGGI PADA MATERI SISTEM PERTAHANAN TUBUH SISWA KELAS XI SMA (Jurnal Bioconcetta, 2019)
This study aims to determine student's high-level thinking skills on the body's defense system topics. Type of research is descriptive qualitative with a population of students of all grade XII MIPA Mathematics and natural sciences totaling 195 people. The sample in this study was taken by the Random Sampling technique, amounting to 39 people. The type of data collection used is a written test consisting of 24 questions consisting of taxonomic levels C4, C5, and C6. Data of high-level thinking skills obtained from the critical thinking skills test by 34%, creative thinking by 52%, problem-solving 30% and decision making by 35%. The result of the ability to analyze by 44%, evaluate by 29% and create by 27%. Based on the results of the study it can be concluded that the ability to think of high-level students is categorized as not good.